2019
DOI: 10.1177/0004867419829228
|View full text |Cite
|
Sign up to set email alerts
|

Association of functioning and quality of life with objective and subjective measures of sleep and biological rhythms in major depressive and bipolar disorder

Abstract: Objective: Disruptions in biological rhythms and sleep are a core aspect of mood disorders, with sleep and rhythm changes frequently occurring prior to and during mood episodes. Wrist-worn actigraphs are increasingly utilized to measure ambulatory activity rhythm and sleep patterns. Methods: A comprehensive study using subjective and objective measures of sleep and biological rhythms was conducted in 111 participants (40 healthy volunteers [HC], 38 with major depressive disorder [MDD] and 33 with bipolar disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 49 publications
4
40
0
Order By: Relevance
“…Additionally, integrated insights give an understanding of how biological rhythm disturbances affect a variety of conditions and biological functions such as—monoamine signaling of mood disorders, the immune system, hypothalamic–pituitary–adrenal (HPA) axis regulation, metabolic peptides, cellular processes (redox, mitochondria, apoptosis, neurogenesis) [9], cerebral parenchyma, suprachiasmatic nucleus [10], and regulation of the biological clock through epigenetic control [11]. Researchers have made an effort, through a variety of measurements and actigraphy, to evaluate biological rhythms in subjects with mood disorders objectively [12,13]. In addition, studies show that correction of biological rhythms through light therapy, behavior modification, and pharmacological agents (such as melatonin) reduces the duration of mood-related symptoms and the severity of other symptoms [14,15], improving the overall quality of life [16].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, integrated insights give an understanding of how biological rhythm disturbances affect a variety of conditions and biological functions such as—monoamine signaling of mood disorders, the immune system, hypothalamic–pituitary–adrenal (HPA) axis regulation, metabolic peptides, cellular processes (redox, mitochondria, apoptosis, neurogenesis) [9], cerebral parenchyma, suprachiasmatic nucleus [10], and regulation of the biological clock through epigenetic control [11]. Researchers have made an effort, through a variety of measurements and actigraphy, to evaluate biological rhythms in subjects with mood disorders objectively [12,13]. In addition, studies show that correction of biological rhythms through light therapy, behavior modification, and pharmacological agents (such as melatonin) reduces the duration of mood-related symptoms and the severity of other symptoms [14,15], improving the overall quality of life [16].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding our literature search, no study was conducted with the BRIAN questionnaire in patients with schizophrenia. The BRIAN was developed with a focus on biological rhythm in patients with the mood disorder [24] and showed promising validity with the objective parameters of circadian rhythmicity, including actigraphy records [43] and level of urinary 6-sulfatoxymelatonin [44]. It also suggested that and subjective measures (BRIAN) provide extensive evidence of sleep and biological rhythm system disruptions in mental disorders [44].…”
Section: Discussionmentioning
confidence: 99%
“…The BRIAN was developed with a focus on biological rhythm in patients with the mood disorder [24] and showed promising validity with the objective parameters of circadian rhythmicity, including actigraphy records [43] and level of urinary 6-sulfatoxymelatonin [44]. It also suggested that and subjective measures (BRIAN) provide extensive evidence of sleep and biological rhythm system disruptions in mental disorders [44]. Also, the BRIAN appears to be a feasible tool to evaluate all domain of biological rhythms, due to the other scales that only indirectly measure biological rhythm by testing seasonality or chronotype or subjective quality of sleep [45].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lam et al 29 and Kennedy et al 30 studied BD subjects in various mood states (depressed, manic, and euthymic) and reported reduced nighttime serum melatonin concentrations compared to healthy control subjects. The study by Kennedy et al found no significant differences depending on mood state and no significant differences in urinary aMT6s levels between BD and healthy control participants, whereas Slyepchenko et al 31 found lower levels of urinary aMT6s levels in BD participants. Nurnberger et al 32 found euthymic patients with BD type I disorder to have lower serum melatonin during dark conditions including a later peak compared to healthy control subjects.…”
Section: Melatonin Measuresmentioning
confidence: 90%